Needs Analysis for Developing an E-Module to Enhance Critical Thinking in Elementary Social Studies Learning - Mulyawati, Yuli; M. Japar; Nurhasanah, Nina (International Conference on Elementary Education, 2025)
This study analyzes learning needs as the foundational basis for developing an electronic module (E-Module) aimed at strengthening elementary students’ critical thinking skills in social studies. The research was conducted in three public elementary schools in Bogor City using a descriptive qualitative design through classroom observations, semi-structured interviews, and questionnaire administration involving 60 students and six teachers. The findings indicate that students’ critical thinking abilities predominantly remain at the lower-order levels of Bloom’s taxonomy. Although 58% of students were able to recall factual information and 61% could restate basic concepts, only 22% demonstrated the ability to apply concepts to novel situations. Moreover, merely 15% were capable of analyzing, and only 8% were able to evaluate social issues presented during instruction. Learning practices are heavily dominated by teacher-centered lectures and textbook dependency, with limited utilization of digital and interactive learning media. Teachers also reported constraints related to insufficient digital resources, limited pedagogicaltechnology integration skills, and challenges in designing inquiry-oriented materials that support higherorder thinking. These conditions underscore the urgent need for pedagogical innovation through the development of digital E-Modules that scaffold reasoning processes, facilitate inquiry-based learning, and promote higher-order thinking in alignment with the competency demands of the Merdeka Curriculum. The outcomes of this needs analysis provide a substantive empirical foundation for subsequent stages of EModule design, particularly the development of culturally responsive and technology-enhanced instructional materials that can improve student engagement, conceptual mastery, and critical thinking performance within the elementary social studies context.